Diagrama causa-efecto de la demora de recepción de paquetes turisticos nacionales e internacionales. - Arias Sarez, Eduardo Adrian (My University, 2020)
The cause – effect diagram is a method used to create and classify ideas about the causes of a problem through a graphic representation. The general objective of this present investigation is to identify the reasons for delay in the reception of tourist packages through the cause-effect diagram in order to visualize the common problems that arise in national and international tourism companies. The methodology that was implemented is qualitative based on secondary data sources by means of a documentary bibliographic review, in this way the study will be complemented with an interview with the managers of the travel agencies “Avial Tours” and “Castro American Tour”. The results made it possible to detect the most common causes that occur in travel agencies with respect to tourist packages, intervening in aspects such as personnel, information, method, system and service capacity, and thus making an improvement plan in order to provide value added to service.
El diagrama causa – efecto es un método que sirve para crear y clasificar ideas sobre las causas de un problema mediante una representación gráfica. El objetivo general de esta presente investigación es identificar los motivos de demora en la recepción de los paquetes turísticos mediante el diagrama causa-efecto con el fin de visualizar los problemas comunes que surgen en las empresas de turismos nacionales e internacionales. La metodología que se implementó es cualitativa basada en fuentes de datos secundarios mediante revisión bibliográfica documental, de esta forma se complementará el estudio con una entrevista a los gerentes de agencias de viajes “Avial Tours” y “Castro American Tour”. Los resultados permitieron detectar las causas más comunes que suceden en las agencias de viajes respecto a los paquetes turísticos, interviniendo aspectos como el personal, información, método, sistema y capacidad de servicio y con ello realizar un plan de mejora al fin de otorgar un valor agregado al servicio.
Keywords: GESTIÓN DE CALIDAD; PAQUETES TURÍSTICOS; DIAGRAMA CAUSA Y EFECTO; NACIONAL E INTERNACIONAL